An improved approach for managing energy efficiency in mobile networks - Radhwan M. Abdullah; Ayad H. Abdulqader; Dia M. Ali; Ali A. Alwan; Abedallah Z. Abualkishik (Institute of Advanced Engineering and Science, 2022)
It is highly expected that soon there will be environmental and economic negative implications from the amount of energy consumed by wireless network devices. Therefore, many researchers have paid attention toward addressing these challenges to investigate the impact of these wireless networks on both environment and the economy. This paper proposes an approach for alternating work among the fifth generation (5G) with Long-Term Evolution (LTE) wireless networks. The idea of the proposed approach relies on turning off specific base stations (BSs) and antennas for the users based on the required quality of service (QoS). Some BSs like 5G networks aim to provide high-speed communications with significant savings in energy consumption during high traffic periods. On the other hand, there is a slow speed with the high consumption of energy in other BSs like LTE networks. Our proposed solution employs the idea of activating some of the BSs networks and changing the number of active antennas that achieves optimal results for the entire area. Doing so lead to a significant reduction in energy consumption when the traffic load is low. The experimental results illustrate that our proposed solution outperforms the most recent approaches by saving a significant amount in power consumption while maintaining a stable service awareness during switching situations.